Time trends (1992-2005) in undernutrition and obesity among children under five years of age in Alagoas State, Brazil Tendencia temporal (1992-2005) de la desnutrición y de la obesidad en menores de cinco años en el estado de Alagoas, Brasil Tendência temporal (1992-2005) da desnutrição e da obesidade em menores de cinco anos no Estado de Alagoas, Brasil - Monica Lopes de Assunção (Cadernos de Saúde Pública, 2013)
The aim of this study was to describe time trends in stunting and obesity in children under five years of age in Alagoas State, Brazil. Two surveys were conducted with representative samples, the first in 1992 (n = 1,228) and the second in 2005 (n = 1,384). Stunting was defined as height-for-age < -2 standard deviations and obesity as weight-for-height > 2 standard deviations. Prevalence of stunting decreased from 22.5% to 11.4% (PR = 0.50; 95%CI: 0.42; 0.60), while obesity increased from 6.7% to 9.3% (PR = 1.36; 95%CI: 1.04; 1.77). During the same period there was a decrease (p ≤ 0.05) in the proportions of the following variables: rural residence, households without running water, households with more than four members, mothers with more than two children, low birth weight, and mother's lack of access to prenatal care. Adjustment for these variables significantly reduced the magnitude of associations, and the 95% confidence included 1.0, suggesting that changes in the prevalence of stunting and obesity were mediated by these characteristics. During the period, there was a striking reduction in the prevalence of stunting and an increase in the frequency of obesity. Se tuvo por objetivo describir la tendencia temporal del déficit de estatura y de la obesidad en menores de 5 años de Alagoas, Brasil. Dos encuestas con muestras representativas fueron realizados en 1992 (n = 1.228) y 2005 (n = 1.384). El déficit de estatura fue definido por la altura/edad < -2 desvíos-padrón y obesidad por peso/altura > 2 desvíos-padrón. La prevalencia de déficit de estatura cambió de un 22,5% a un 11,4% RP = 0,50; IC95%: 0,42; 0,60), mientras que la de obesidad pasó de un 6,7% a un 9,3% (RP = 1,36; IC95%: 1,04; 1,77). En el mismo período hubo una reducción (p ≤ 0,05) en las proporciones de las siguientes variables: habitantes en la zona rural, familias sin acceso al agua corriente, domicilios con más de cuatro personas, madres con más de dos hijos, bajo peso al nacer y madres sin acceso al servicio prenatal. El ajuste para esas variables redujo significantemente la magnitud de las asociaciones y los IC95% englobaron la unidad, sugiriendo que los cambios en las prevalencias de desnutrición y obesidad fueron mediados por esas características. En el período evaluado hubo una drástica reducción en la prevalencia de déficit de estatura e incremento en la frecuencia de obesidad. Objetivou-se descrever a tendência temporal do déficit estatural e da obesidade em menores de 5 anos de Alagoas, Brasil. Dois inquéritos com amostras representativas foram realizados em 1992 (n = 1.228) e 2005 (n = 1.384), respectivamente. Déficit estatural foi definido pela altura/idade < -2 desvios-padrão e obesidade por peso/altura > 2 desvios-padrão. A prevalência de déficit estatural mudou de 22,5% para 11,4% (RP = 0,50; IC95%: 0,42; 0,60), enquanto a de obesidade passou de 6,7% para 9,3% (RP = 1,36; IC95%: 1,04; 1,77). No mesmo período houve redução (p ≤ 0,05) nas proporções das seguintes variáveis: moradores na zona rural, famílias sem acesso à água encanada, domicílios com mais de quatro pessoas, mães com mais de dois filhos, baixo peso ao nascer e mães sem acesso ao pré-natal. O ajuste para essas variáveis reduziu significantemente a magnitude das associações e os IC95% englobaram a unidade, sugerindo que as mudanças nas prevalências de desnutrição e obesidade foram mediadas por essas características. No período avaliado houve drástica redução na prevalência de déficit estatural e incremento na frequência de obesidade.